ENVIRONMENTAL CONSEQUENCES OF INTENSIVE AGRICULTURAL ACTIVITY AND WAYS OF SUSTAINABLE AGRICULTURE - KRYVOKHYZHA, YEVHEN; YEMETS, ZOIA (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The article analyzes the impact of intensification of agricultural production on the ecological state. It is indicated that the intensification of agriculture has a negative impact on the environment, mainly due to negative external environmental impacts. The need to introduce more ecologically oriented agricultural technologies and environmental monitoring is emphasized. It is highlighted that with the deterioration of the ecological state, it is necessary to rethink the strategy of agricultural intensification, paying attention to the development of infrastructure and processing industry, which will contribute to an effective and resource-saving direction of sustainable development.The article argues that the basis of agricultural development should be ecological orientation, taking into account the natural characteristics and possibilities of natural resources. An ecological approach is proposed as an alternative solution to environmental problems in the agricultural sector, as compensation for the use of natural resources. Prevention of soil erosion, application of organic fertilizers, use of soil protection technologies are measures that improve the quality of soils and provide an ecologically mild impact. Minimizing the man-made load on natural resources due to the intensification of the use of agricultural machinery, reducing the pressure on the soil from wheeled and crawler tractors, limiting the passage of machinery through the fields and introducing ecologically safe land cultivation systems will allow solving the problems of soil hydrological regime disturbance. It was determined that agricultural lands, which have been severely affected by human activity and destructive natural phenomena, should be excluded from active cultivation. It is emphasized that preservation of biodiversity is a key aspect for environmental protection. The role of agrarian systems in ensuring high productivity of rural production and their impact on species diversity helps to realize the importance of the concept of sustainable development.
Keywords: intensive agricultural activity; biodiversity; environmental problems; agroecosystem; environmentalization; natural fertility